O estágio supervisionado na formação docente - Santana, Andreia da Cunha Malheiros; Inforsato, Edson do Carmo [UNESP] (My University, 2011)
The aim of this article is to study the supervised apprenticeship in a bachelor degree, more specifically the Literature and Language degree in São Paulo State University (UNESP), in Araraquara. Many students conclude their courses with no idea about what they’ll face in public schools. The reality has shown us that our bachelor degrees aren’t reaching their objectives. Looking for a theoretical support, it’s possible to infer this is not a recent problem, but an ancient one that has been discussed for a long time. In a wide context that involves the depreciation of bachelor degree, the aim of this article is to study the supervised apprenticeship in a bachelor degree, considering the opinion of the undergraduates, teachers from public school, who receive the undergraduates in their classroom and professors who are responsible for training them at the university. The supervised apprenticeship will receive more emphasis in the context it’s insert, with the intent of centralize the study in a very important part of the teacher training. Meanwhile, it’s the only responsible for the faults on pedagogical training of the teacher. It’s necessary to rethink the bachelor degree, not only as a project in the pedagogical area, but as responsibility of all the professors involved. Undergraduate a Language teacher is a project that must involve every area.

Este trabalho tem como principal objetivo estudar o estágio supervisionado dentro de um curso de licenciatura, tendo como local escolhido para observação o curso de Letras da Faculdade de Ciências e Letras do Câmpus de Araraquara. Muitas vezes, o graduando sai da graduação sem imaginar o que vai encontrar, o que mostra que os cursos de formação de professores não estão atendendo a todos os seus objetivos. Ao buscar um respaldo teórico para entender esta realidade, foi possível perceber que a situação não é recente e que o problema há muito já vem sendo discutido.Dentro do amplo cenário que envolve a desvalorização dos cursos de licenciatura, este trabalho pretende focalizar seus estudos no que se relaciona ao estágio, entretanto, isto não significa que ele seja o único responsável pelas falhas na formação pedagógica do professor, mas que será dada mais ênfase a ele no contexto em que está inserido, com o intuito de centralizar o estudo num dos vértices bastante importante da formação docente. É necessário que o curso de licenciatura seja repensado, não como um projeto exclusivo da parte pedagógica, mas como responsabilidade de todos os docentes envolvidos no curso. Formar um professor no curso de Letras, ou em qualquer outra área do conhecimento num projeto que envolva todas as áreas.
The supervised apprenticeship on teacher’s training
Keywords: Under graduation course; supervised apprenticeship; Teacher training; Licenciatura; Estágio Supervisionado; Formação de Professores